Recurrent sepsis and neuroinvasive disease in a neonate culture-positive for a Group B Streptococcus CPS III serotype, hvgA+ strain. Issue 3 (25th June 2016) - Suresh, Sneha; Tyrrell, Gregory; Alhhazmi, Areej; Escoredo, Sandra; Hawkes, Michael
Abstract : Introduction: Late-onset disease with Group B Streptococcus (GBS LOD) remains a significant problem in neonates. Unlike early-onset disease, rates of GBS LOD have not changed with prenatal testing. Effects of GBS LOD can be severe and thus identifying risk factors for severe GBS LOD, such as hypervirulence genes, may help in managing these infants. Case presentation: We present a case of a neonate with capsular serotype III GBS sepsis without meningitis that recurred 6 days after a 10-day-treatment period with IV ampicillin. The second episode was characterized by sepsis, neuroinvasion, meningitis and subsequent profound encephalomalacia. The short duration between the two episodes suggested recrudescence rather than reinfection. The GBS isolate was ultimately found to be positive for hypervirulence gene hvgA+, which encodes for a protein known to mediate meningeal tropism and neuroinvasion. Conclusion: hvgA positivity may thus potentially serve as an important biomarker for severe and neuroinvasive GBS LOD that can influence treatment decisions.